The Military Frontier in Croatia and the Triplex Confinium - Roksandić, Drago (2007)
An overview of the current researches on the history of the Military Border in Croatia has been made, as well as an overview of the researches intergrating the Military Border with the civil provinces of Croatia and the Habsburg lands of the time. Special attention has been focus upon the Triplex Confinium researches, as well as approaches and methods used (comparative history, intercultural/transcultural comparison), etc.